Sensitive fluorimetric method based on sequential injection analysis technique used for dissolution studies and quality control of prazosin hydrochloride in tablets - Legnerová, Z; Huclová, J; Thun, R; Solich, P (Journal of pharmaceutical and biomedical analysis, 2004)
This report introduces a fully automated flow system for drug-dissolution studies based on the coupling of the sequential injection analysis (SIA) technique with a conventional dissolution apparatus. The methodology described was used for monitoring of dissolution profiles of prazosin hydrochloride (PRH) in pharmaceutical formulation. The very sensitive fluorimetric detection of PRH was performed at lambda(ex)=244 nm (lambda(em)>or=389 nm). Under the optimal conditions, the calibration curve was linear over the range 0.02-2.43 mg x l(-1) of PRH with R.S.D. 1.89, 1.23, and 1.80% (n=10) when determining 0.02, 1.22, and 2.43 mg x l(-1) of PRH in standard solutions, respectively. Equation of the calibration curve was calculated giving the following values: F=4.108 c-3.9 (n=6), r=0.9996. Detection limit was calculated 0.007 mg x l(-1) of PRH. The dissolution test of Deprazolin tablets was programmed for 60 min, with a continuous sampling rate of 70 h(-1) under conditions required by USP 26. Results obtained by SIA technique compared well with HPLC standard method.
Keywords: vysokoúčinná kapalinová chromatografie; Spectrophotometry, Ultraviolet; Chromatography, High Pressure Liquid; Prazosin; Flow Injection Analysis; Quality Control; spektrofotometrie ultrafialová; Tablets; Solubility; průtoková injekční analýza; tablety; rozpustnost; prazosin; řízení kvality